Nasopharyngeal Carcinoma (NPC) Related Human Leukocyte Antigen (HLA) Haplotype Sharing among Southern East Asian Population - Rika Yuliwulandari; Katsushi Tokunaga (Universitas Islam Bandung, 2017)
The human leukocyte antigens (HLAs) play important roles in the immune systems to response to various pathogens and disease among individuals. The aim of this study was analyze the HLA allele and haplotype frequencies of Southern East Asian population that show high incidence of nasopharyngeal carcinoma (NPC) to evaluate the shared HLA haplotype contribution to NPC susceptibility among the population and analyses the genetic affinities between the population. We collect information of HLA haplotype from our previous study, other published paper, and HLA database in 19 population during 2005 to 2015. Haplotype frequencies were estimated using the maximum likelihood method based on an expectation maximization algorithm with ARLEQUIN v.2.0 software. We also calculated the genetic distance among 19 Southern East Asians based on HLA allele frequency using modified Cavalli-Sforza (DA) distance method. Then, a phylogenetic tree was constructed using DISPAN software and principal component analysis (PCA) was performed using XLSTAT-PRO software. A33-B58-DR3 haplotype, tightly linked to NPC, was commonly observed in all populations, supporting the high incidence of NPC in the populations. In addition, A2-B46 haplotype also associated with NPC, was also commonly found in several population that may also have a role in the disease development. The conclusion is the HLA haplotype sharing has an important role than the HLA allele sharing. The A33-B58-DR3 haplotype and A2-B46-DR9 haplotype in this study could be related to NPC in the Southern East Asian populations. The observed haplotype needs to be tested in the real patients to confirm the assumptionPENYEBARAN HAPLOTIPE HUMAN LEUKOCYTE ANTIGEN (HLA) TERKAIT NASOPHARYNGEAL CARCINOMA (NPC) PADA POPULASI ASIA TIMUR BAGIAN SELATANHuman leukocyte antigens (HLAs) berperan penting dalam sistem imun untuk merespons berbagai patogen dan penyakit di antara individu yang berbeda. Tujuan penelitian ini menganalisis frekuensi alel dan haplotipe HLA populasi Southern East Asia yang menunjukkan insidensi yang tinggi terhadap nasopharyngeal carcinoma (NPC) untuk mengevaluasi kerentanan NPC bagi individu. Informasi haplotipe HLA dikumpulkan dari studi sebelumnya, publikasi jurnal internasional, dan database HLA pada 19 populasi dalam periode tahun 2005–2015. Frekuensi haplotipe dihitung menggunakan metode maximum likelihood berdasarkan expectation maximization algorithm menggunakan piranti lunak ARLEQUIN v.2.0. Jarak genetik di antara 19 populasi Southern East Asians dihitung menggunakan metode modified Cavalli-Sforza (DA) distance. Kemudian, pohon filogenetik dikonstruksi dengan metode neighbor-joining (NJ) menggunakan piranti lunak DISPAN. Principal component analysis (PCA) dilakukan menggunakan piranti lunak XLSTAT-PRO. Haplotipe A33-B58-DR3 terkait erat dengan NPC yang biasa terlihat di semua populasi mendukung tingginya insidensi penyakit dalam populasi. Selain itu, haplotipe A2-B46 juga terkait dengan NPC yang juga ditemukan pada beberapa populasi sehingga kemungkinan memiliki peran dalam perkembangan penyakit. Pada kasus NPC, haplotipe HLA lebih berperan dibanding dengan alel HLA. Haplotipe A33-B58-DR3 dan haplotipe A2-B46-DR9 yang ditemukan terkait dengan NPC pada populasi Southern East Asia. Haplotipe yang diamati tersebut perlu diuji pada pasien nyata untuk mengonfirmasi simpulan.